PENGARUH KESEIMBANGAN KEHIDUPAN KERJA TERHADAP DISIPLIN KERJA: (STUDI KASUS PADA MAHASISWA KELAS KARYAWAN SEMESTER AKHIR SEKOLAH TINGGI ILMU EKONOMI SUTAATMADJA SUBANG) - Mutqi Sopiawadi; Gugyh Susandy; Indah Ayu Lestari (STIESA Press, 2022)
This study aims to determine the effect of work-life balance on work discipline in the final semester students of STIE Sutaatmadja Subang. The research method used is a quantitative method using the SPSS program. The data used in this study are primary data obtained from interviews and questionnaires. By using 35 respondents. The analysis technique used is a simple linear regression analysis technique. Based on the results of the study, it is known that work life balance has a positive effect on work discipline. So the ability to balance time is needed both in terms of work and outside of work. To achieve balance and strengthen work discipline, it is necessary Work-life balance, attitudes, norms and responsibilities in one's life.